When do defaults stick and when are they ethical? Taxonomy, sytematic review and design recommendations - Dominic Lemken (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2020)
In many instances, default nudges are proven to be strong drivers of behavior. However, a number of ethical concerns have been raised. Both, nudge success and ethical concerns, depend heavily on the features of the default nudge, with some of them being shared by defaults in all settings. We systematically review the scientific literature on default nudges from various disciplines and investigate nudge success and ethical concerns with respect to seven main features: (1) the initial state of the choice architecture, (2) the invasiveness, (3) the psychological effect mechanism, (4) the purpose, (5) the visibility, (6) the customization, and (7) the disclosure of the default. When designing a default, as researcher or practitioner, a full consideration of these features is advised. Often enough, choice architects are not aware of the design options. In a nutshell, the welfare losses suffered through the initial choice architecture are often overlooked. Customizations and disclosures of defaults are scarcely used despite easing ethical concerns without negatively affecting nudge success. The psychological effect mechanism, with several ethical implications, remains a theoretical relict that is not empirically researched. Default framing in combination with a choice structuring default can lead to greater nudge success.
Keywords: M38; I12; I38; 330; nudging; opt-out; opt-in; status quo; choice architecture; defaulting; welfare